Trophoblast uptake of DBP regulates intracellular actin and promotes matrix invasion. Issue 1 (April 2021) - Ganguly, Ankana; Tamblyn, Jennifer A; Shattock, Alexandra; Joseph, Annsha; Larner, Dean P; Jenkinson, Carl; Gupta, Janesh; Gross, Janesh R; Hewison, Martin
Abstract : Early pregnancy is characterised by elevated circulating levels of vitamin D binding protein (DBP). The impact of this on maternal and fetal health is unclear but DBP is present in the placenta, and DBP gene variants have been linked to malplacentation disorders such as preeclampsia. The functional role of DBP in the placenta was investigated using trophoblastic JEG3, BeWo and HTR8 cells. All three cell lines showed intracellular DBP with increased expression and nuclear localisation of DBP in cells treated with the active form of vitamin D, 1, 25-dihydroxyvitamin D (1, 25D). When cultured in the serum of mice lacking DBP (DBP−/−), JEG3 cells showed no intracellular DBP indicating uptake of exogenous DBP. Inhibition of the membrane receptor for DBP, megalin, also suppressed intracellular DBP. Elimination of intracellular DBP with DBP−/− serum or megalin inhibitor suppressed matrix invasion by trophoblast cells and was associated with increased nuclear accumulation of G-actin. Conversely, treatment with 1, 25D enhanced matrix invasion. This was independent of the nuclear vitamin D receptor but was associated with enhanced ERK phosphorylation, and inhibition of ERK kinase suppressed trophoblast matrix invasion. When cultured with serum from pregnant women, trophoblast matrix invasion correlated with DBP concentration, and DBP was lower in first-trimester serum from women who later developed preeclampsia. These data show that the trophoblast matrix invasion involves uptake of serum DBP and associated intracellular actin-binding and homeostasis. DBP is a potential marker of placentation disorders such as preeclampsia and may also provide a therapeutic option for improved placenta and pregnancy health.